1998
DOI: 10.1002/(sici)1097-0185(199801)250:1<62::aid-ar6>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous distribution of soluble guanylate cyclase in the pulmonary vasculature of the fetal lamb

Abstract: Background: Vascular segments in the fetal lung differ anatomically and functionally from one another. At birth, the nitric oxide (NO) pathway plays an integral role in reducing pulmonary vascular resistance through a marked vasodilation. However, the contributions of each vascular segment to this dilation are unclear. We sought to determine the distribution of soluble guanylate cyclase (sGC), the enzyme NO activates to induce vasodilation across the pulmonary vasculature. Methods: Pulmonary airspaces were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Our immunohistochemical results were in general agreement with results by single immunolabeling for NOS-III (Halbower et al 1994) and sGC (a1 subunit) (D'Angelis et al 1998) within pulmonary vasculature of the ovine fetus. Different from their studies, the exact colocalization of these two enzymes showed on the same tissue section by our double immunolabeling technique demonstrated directly anatomic evidence of a paracrine role of these two key enzymes in the NO/cGMP pathway within fetal pulmonary vasculature.…”
Section: Discussionsupporting
confidence: 89%
“…Our immunohistochemical results were in general agreement with results by single immunolabeling for NOS-III (Halbower et al 1994) and sGC (a1 subunit) (D'Angelis et al 1998) within pulmonary vasculature of the ovine fetus. Different from their studies, the exact colocalization of these two enzymes showed on the same tissue section by our double immunolabeling technique demonstrated directly anatomic evidence of a paracrine role of these two key enzymes in the NO/cGMP pathway within fetal pulmonary vasculature.…”
Section: Discussionsupporting
confidence: 89%
“…For example, vascular segments in the fetal sheep lung have been shown to differ anatomically and functionally from one another. Immunostaining for soluble guanylate cyclase showed very weak to no staining in large arteries but intense staining in distal arteries, implying a greater role for NO-mediated vasodilation in smaller arteries (11). Because vessels were precontracted with K ϩ depolarization, we are not able to comment on endothelium-derived hyperpolarizing factor-dependent mechanisms.…”
Section: Ach-induced Responsesmentioning
confidence: 92%
“…29 Like NOS3, pulmonary sGC expression undergoes dramatic changes during the transition from the fetal lung to the adult lung. sGC is abundant in VSMCs of the pulmonary resistance vessels of fetal and perinatal animals, 30,31 with peak activity in the perinatal period suggesting a role in the acute drop in pulmonary vascular resistance (PVR) after birth. sGC expression and activity decrease in the adult.…”
Section: Role Of No In the Pulmonary Vascular Transition At Birthmentioning
confidence: 99%